Microwave‐Assisted Suzuki–Miyaura and Sonogashira Coupling of 4‐Chloro‐2‐(trifluoromethyl)pyrido[1, 2‐e]purine Derivatives. Issue 33 (6th August 2019) - Tber, Zahira; Biteau, Nicolas G.; Agrofoglio, Luigi; Cros, Julien; Goffinont, Stéphane; Castaing, Bertrand; Nicolas, Cyril; Roy, Vincent
Abstract : The convenient preparation of three imidazo[1, 2‐ a ]pyridine‐2‐carboxamide intermediates is reported through known Strecker–Ugi type multicomponent reactions, Tschitschibabin type condensations, and further synthetic sequences. The derivatives were then efficiently converted to novel 4‐chloro‐2‐(trifluoromethyl)pyrido[1, 2‐ e ]purines by their original reactions with 2, 2, 2‐trifluoroacetamide, followed by subsequent dehydroxychlorination reactions. These compounds were cross‐coupled under microwave irradiation through SuzukiMiyaura and Sonogashira palladium(0) catalysis to various aromatic and alkynyl reagents, thus providing the related C‐4 substituted pyrido[1, 2‐ e ]purines of biological interest in good yields. Abstract : The convenient preparation of novel 4‐chloro‐2‐(trifluoromethyl)pyrido[1, 2‐ e ]purines by the original reactions of imidazo[1, 2‐ a ]pyridine‐2‐carboxamides and 2, 2, 2‐trifluoroacetamide is reported. The derivatives were then efficiently cross‐coupled through Suzuki–Miyaura and Sonogashira catalysis to give the related C‐4 substituted pyrido[1, 2‐ e ]purines of biological interest in good yields.